THE IMPACT OF TRAUMA AND MEMORY IN THE FARMING OF BONES STORY IN THE DEW BREAKER (Modern education and development, 2024)
This article examines how Farming of Bones story addresses the lasting psychological impact of political violence on survivors and their communities. Through the experiences of the protagonist, Amabelle Desir, Danticat weaves a narrative that reflects on the complexity of identity, particularly in the context of the Haitian-Dominican divide. The novel highlights the fragmented nature of memory and the role of storytelling in preserving collective history. The novel emphasizes the power of memory to resist erasure and serves as a reminder of the importance of acknowledging past atrocities for reconciliation and survival.